LATIHAN POSISI KNEE CHEST UNTUK PENATALAKSANAAN POSISI LETAKLINTANG PADA IBU I G3P2A0 KEHAMILAN 35 MINGGU DI ACEH BARAT - Azizah, Rohadatul; Zahara, Evi; Asmanidar, Asmanidar; Yushida, Yushida (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Introduction: Transverse lie is when the fetus's longitudinal axis crosses the mother's longitudinal axis perpendicularly or approaches 900. To change the position of the fetus from the transverse lie (transverse) to the head position (normal), pregnant women can do the knee chest position or doubling. This position helps the fetus rotate and return to its normal position, with the head down. This exercise is done routinely for several minutes, several times a day. The use of the knee chest position can be considered so that the incidence of Sectio Caesarea (CS) decreases, so that maternal morbidity and mortality can decrease. The method used is a case report, with an obstetric management approach and using the SOAP documentation method (Subjective, Objective, Analysis, Management). Data collection techniques use interview techniques, physical examinations, documentation studies, and literature studies. The subject in this study was Mrs. I, 33 years old, G3P2A0, 35 weeks of gestation with a transverse lie. The results of the study showed a diagnosis in the case of Mrs. I, 33 years old, G3P2A0, 35 weeks of gestation with a doubling presentation. Results: The results of the study showed that after being given care in the form of applying knee chest position therapy as an effort to change the baby's transverse position to a normal position during pregnancy. Conclusion: Care Implementing the knee chest position can change the baby's transverse position back to normal